2021
DOI: 10.3390/agriculture11121192
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Perception of Entrepreneurial Success: Evidence from the Greek Reality

Abstract: The purpose of this paper is to evaluate the perceptions of Greeks-farmers regarding success and to investigate the factors that are considered as indicators to explain, predict, and determine perceptional entrepreneurial success. This research focuses on existing agricultural enterprises as more than 400 randomly selected agricultural enterprises compose the survey’s sample. The main research method is through structured questionnaires. A series of multivariate analyses were conducted to examine the data. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Many authors acknowledge that the self-reported nature of this variable does not measure actual success, but rather focuses on how satisfied the entrepreneur is with his or her personal life and business achievements [3,9,11] . This kind of success can be perceived differently by individuals and depends on many factors [4,5,10,15] .…”
Section: Entrepreneurial Successmentioning
confidence: 99%
See 4 more Smart Citations
“…Many authors acknowledge that the self-reported nature of this variable does not measure actual success, but rather focuses on how satisfied the entrepreneur is with his or her personal life and business achievements [3,9,11] . This kind of success can be perceived differently by individuals and depends on many factors [4,5,10,15] .…”
Section: Entrepreneurial Successmentioning
confidence: 99%
“…Recent research has attempted to explain the causes of success in terms of predictors related to the entrepreneur's personality, education, age, personal and family security, relationships with employees and stakeholders, social value creation, self-realization and spirituality, which are important indicators of the owner-manager's overall wellbeing [2] . Other variables such as specific business characteristics (years of operations, economy sector, sales stratum) and environmental conditions faced by the business [3,9,11] .…”
Section: Entrepreneurial Successmentioning
confidence: 99%
See 3 more Smart Citations